ECONOMIC OPENNESS AND ITS IMPACT IN THE GROWTH OF THE ALGERIAN ECONOMY DURING THE PERIOD (1970-2012) - Bilal Louail (European Scientific Journal, ESJ, 2015)
This study aims to clarify the relationship between openness and growth of the Algerian economy during the period (1970-2012), and according to a series of studies that have proved a causal relationship between openness and economic growth. Our study end up to the existence of significant correlation between the openness of the Algerian economy and the evolution of its Gross Domestic Product, that is the Algerian GDP growth leads to attract foreign capital which is known by the name of Foreign Direct Investment, which in turn contributes to the opening up of the Algerian economy, and the latter, is influenced by Gross Domestic Product and other determinants like inflation and the real exchange rate, trade openness and infrastructure, where the study proved the existence of a positive impact on trade openness, and an expected negative impact on both inflation and the real exchange rate, and an unexpected negative impact on the infrastructure.